The role of age in ocular toxoplasmosis: clinical signs of immunosenescence and inflammaging - Eraghi, Armin Taghavi; Garweg, Justus G.; Pleyer, Uwe (Frontiers in Medicine, 2024)
Purpose This study aimed to investigate the association between age, immune response, and clinical presentation of ocular toxoplasmosis (OT). Design This was a monocentric, retrospective, observational cohort study. Methods A review of the medical records of patients with active OT at the Uveitis Center, Charité Universitätsmedizin, was conducted. Baseline parameters included age at presentation, visual acuity, intraocular pressure (IOP), size and location of active lesions, inflammatory activity, antibody index (AI), and complications of intraocular inflammation. The data were presented as the mean ± standard deviation (SD). The level of significance was set at a p-value of <0.05. Results Between 1998 and 2019, 290 patients with active OT were diagnosed at our tertiary reference center. The mean age of the participants was 37.7 ± 17.1 years, 53.8% of them were female individuals, and 195 patients (70.9%) showed recurrent disease. Older age was associated with lower baseline visual acuity (p = 0.043), poor visual outcome (p = 0.019), increased inflammatory activity (p < 0.005), and larger retinal lesions (p < 0.005). Older patients presented a lower AI (<35 years: 45.1 ± 82.7, median: 12.1; ≥35 years: 18.6 ± 50.5, median: 5.8; p = 0.046), confirmed by a decrease in AI with increasing age (R2 = 0.045; p = 0.024). Finally, AI was correlated with lesion size (multiple linear regression analysis: p = 0.043). Macular involvement (24.3% of patients) was positively correlated with complications (macular/peripapillary edema and retinal detachment, p < 0.005) and poor visual outcome (p < 0.005) and was negatively correlated with inflammatory activity (p < 0.005). Conclusion We found a strong and clinically relevant impact of age on the clinical presentation and course of OT. While an unspecific inflammatory response increased with age, the specific, local humoral immune response declined. These findings are well in line with the concept of immunosenescence and inflammaging in uveitis.